Rapid detection of Vibrio alginolyticus in seafood using the flgL gene and real-time polymerase chain reaction - Muktiningsih Nurjayadi; Gladys Indira Putri; Jefferson Lynford Declan; Ismaya Krisdawati; Dandy Akbar Juliansyah; Maharanianska Azzahra; Irvan Maulana; Irma Ratna Kartika; Fera Kurniadewi; Tiara Fahriza; Adinda Myra Amalia Putri; Ayu Berkahingrum; Atikah Nur Rahmawati; Rosita Gio Anggraeni; Dalia Sukmawati; Sri Rahayu; Vira Saamia; I Made Wiranatha; Bassam Abomoelak; Hesham Ali El-Enshasy (Acta Biochimica Indonesiana, 2024)
Background: Seafood is highly nutritious but poses health risks when contaminated with pathogenic bacteria like Vibrio alginolyticus, which causes food poisoning and can infect marine animals and humans. Objective: This research aimed to determine the sensitivity and specificity of real-time polymerase chain reaction (rt-PCR) using the flgL primer pair to detect V. alginolyticus bacteria in seafood. Methods: The rt-PCR method was used to detect V. alginolyticus quickly, specifically, and sensitively. The flgL primer pair was evaluated for amplicon length, Ct value, Tm value, and its ability to differentiate between target and non-target bacteria. In this research, the samples tested were red snapper and blood clams. Results: The flgL primer produced an amplicon length of 224 bp. At 50 ng concentration, it yielded a Ct value of approximately 11.00 and a Tm of approximately 83°C. The flgL primer successfully differentiated between target and non-target bacteria. In sensitivity tests, it detected V. alginolyticus at concentrations as low as 1.86 x 10-3 ng/µL. Detection in seafood samples was also successful. Conclusion: The rt-PCR assay using the flgL primer pair effectively detects Vibrio alginolyticus in seafood with high specificity, sensitivity, and rapidity. These findings support its use for rapid and accurate detection of pathogenic bacteria in seafood.